Post-translational regulation of endothelial nitric oxide synthase in vascular endothelium - Qian, Jin; Fulton, David (Frontiers in Physiology, 2013)
Nitric oxide (NO) is a short-lived gaseous signaling molecule. In blood vessels, it is synthesized in a dynamic fashion by endothelial nitric oxide synthase (eNOS) and influences vascular function via two distinct mechanisms, the activation of soluble guanylate cyclase (sGC)/cGMP-dependent signaling and the S-nitrosylation of proteins with reactive thiols (S-nitrosylation). The regulation of eNOS activity and NO bioavailability is critical to maintain blood vessel function. The activity of eNOS and ability to generate NO is regulated at the transcriptional, posttranscriptional, and posttranslational levels. Post-translational modifications acutely impact eNOS activity and dysregulation of these mechanisms compromise eNOS activity and foster the development of cardiovascular diseases. This review will intergrate past and current literature on the post-translational modifications of eNOS in both health and disease.